The Validation of QUEFTS model for nutrient management of potato (Solanum tuberosum) in humid south-eastern plains of Rajasthan - NAGAR, B L; BAIRWA, R K; SINGH, JAGDISH; YADAV, D L (The Indian Journal of Agricultural Sciences, 2023)
The crop/cultivar and location-specific management of nutrients, considering soil supply and plant demand of nutrients according to spatial and temporal variations are possible through the use of models such as Quantitative Evaluation of Fertility on Tropical Soils (QUEFTS) model. The experiment was conducted to validate QUEFTS model for fertilizer management to achieve higher productivity of potato (Solanum tuberosum L.) cv. Kufri Bahar in the humid south-eastern plain of Rajasthan during winter (rabi) season 2020–21 and 2021–22. The results revealed that the tuber yield with application of 100% NPK as per QUEFTS model (T5) was 5.64% higher than fertilizer application as per soil test based 100% NPK recommendation for potato, whereas fertilizer application @125% NPK as per QUEFTS model (T6) was 16.5% higher than the T3 (125% NPK of RDF) treatment. However, use of 125% NPK as per QUEFTS model gave significantly higher emergence per cent, grade-wise tuber yield, and grade-wise numbers of potato tuber. On the pooled basis, higher values of gross income, net gain, and cost-benefit (B:C) ratio were observed with use of 125% NPK as per QUEFTS model. The results revealed that QUEFTS model may improve the nutritional quality and sustainability of potato production through site specific nutrient management by building improved fertilizer recommendations.